A double-blind, randomized, placebo-controlled proof of concept study of the efficacy and safety of Lu AF11167 for persistent negative symptoms in people with schizophrenia - Meyer-Lindenberg, Andreas; Nielson Arendt, Jacob; Such, Pedro; Lemming, Ole Michael; Zambori, Janos; Buller, Raimund; Goltz, Christoph von der (European neuropsychopharmacology, 2022)
Lu AF11167 is a selective, high-affinity inhibitor of PDE10A that modulates dopamine D1 and D2 receptor-mediated intraneuronal signalling without binding to these receptors. This randomized, double-blind, parallel-group, placebo-controlled study (NCT03793712) with open-label extension (NCT03929497) evaluated the efficacy of two fixed-flexible doses (1-2mg/day and 3-4mg/day) of Lu AF11167 in stable, non-acute patients with schizophrenia and persistent prominent negative symptoms. The studies were discontinued following a futility analysis of the double-blind study, and we report data collected up to study termination. Of the 210 patients screened, 162 were randomized, 111 completed the double-blind study and 96 entered the open-label study before early termination. The withdrawal rate due to impending relapse was low and comparable across treatment groups (n = 2-4 per group in the double-blind study and n = 1 in the open-label extension). Double-blind treatment with Lu AF11167 3-4mg was not superior to placebo in the reduction of Brief Negative Symptom Scale (BNSS) total scores from Baseline to Week 12 (primary endpoint); adjusted mean changes were -6.8 with placebo, -5.7 with Lu AF11167 1-2 mg group and -6.0 with Lu AF11167 3-4mg. Treatment with Lu AF11167 1-2mg also failed to separate from placebo on the primary endpoint. Neither dose group showed significant improvements versus placebo on any of the secondary efficacy measures exploring effect of treatment on overall symptomology, negative symptoms, positive symptoms, or functioning. Administration of Lu AF11167 was safe and well tolerated and adverse events were not a major reason for withdrawal from the study.